2011
DOI: 10.1186/1687-4722-2011-2
|View full text |Cite
|
Sign up to set email alerts
|

Semitone frequency mapping to improve music representation for nucleus cochlear implants

Abstract: The frequency-to-channel mapping for Cochlear implant (CI) signal processors was originally designed to optimize speech perception and generally does not preserve the harmonic structure of music sounds. An algorithm aimed at restoring the harmonic relationship of frequency components based on semitone mapping is presented in this article. Two semitone (Smt) based mappings in different frequency ranges were investigated. The first, Smt-LF, covers a range from 130 to 1502 Hz which encompasses the fundamental fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…For instance, if the distance between the harmonics were increased, it may be possible to resolve the harmonic structure of complex tones and subsequently pitch perception may be improved. Omran et al (2011) used frequency expansion, and their results showed improved pitch difference limens in NH listeners who were tested with vocoder sounds. Kasturi and Loizou (2007) also showed improvements in melody recognition with such expansion in CI users.…”
Section: F Potential Improvements Of Cis To Enhance Musicmentioning
confidence: 99%
“…For instance, if the distance between the harmonics were increased, it may be possible to resolve the harmonic structure of complex tones and subsequently pitch perception may be improved. Omran et al (2011) used frequency expansion, and their results showed improved pitch difference limens in NH listeners who were tested with vocoder sounds. Kasturi and Loizou (2007) also showed improvements in melody recognition with such expansion in CI users.…”
Section: F Potential Improvements Of Cis To Enhance Musicmentioning
confidence: 99%
“…Auch Musiktraining kann sich positiv auf den Musikgenuss auswirken [6,29,30]. Es gibt verschiedene Ansätze, durch verbesserte Filter, Signalcodierung und -verarbeitung das Musikhören zu verbessern [31,32,33,34]. Andere Arbeitsgruppen nutzen die Erkenntnisse über das Musikhören mit dem CI, um maßgeschneiderte Musikkreationen für CI-Träger*innen zu entwickeln [28,35].…”
Section: Introductionunclassified
“…These encompass music rehabilitation and training as described for instance by Galvin et al (2009), Looi et al (2012), and Fuller et al (2018) as well as novel music compositions (Innes-Brown et al, 2012, Nogueira and Herrera, 2015). Also novel implantation techniques (Hochmair et al, 2015), improved signal coding (Omran et al, 2011; Müller et al, 2012; Todd et al, 2017) and signal preprocessing methods have been proposed.…”
Section: Introductionmentioning
confidence: 99%